A feasibility study on low-dose mindfulness-based stress reduction intervention among prediabetes and diabetes patients - Tong Xia; Snehal Lopes; Liwei Chen; Rebecca Roth; Heidi Zinzow; Karyn Jones; Lingling Zhang; Lu Shi; Meenu Jindal (Elsevier, 2022)
Objectives: To investigate the feasibility of delivering a low-dose mindfulness-based stress reduction (MBSR) intervention among prediabetes/diabetes patients in a clinical setting. Design and setting: This was a single-arm, mixed methods, feasibility study among prediabetes/diabetes patients at a healthcare center in United States. Intervention: The low-dose MBSR intervention was delivered in group format over 4 waves and each wave comprised 8-10 h of 8 sessions over 6-8 weeks. Main outcome measures: We evaluated recruitment, adherence, and attrition rates, participants' satisfaction, motivation and barriers of low-dose MBSR. Psychological, behavioral, and physical measures were compared between pre- and post-intervention. Results: We enrolled 19 participants of 34 eligible individuals with a recruitment rate of 55.9%. Among 19 enrolled participants, 4 dropped out after baseline data collection and did not attend any session and 1 attended one session but did not finish post-intervention data collection, resulting in an attrition rate of 26.3%. Among 15 participants attending at least one session, 46.7% attended all sessions and 80.0% attended at least 5 sessions. Qualitative analysis among 11 participants indicated that 90.9% had positive overall experience with the intervention. Compared to pre-intervention, there was a significant reduction in depression score (mean reduction = 5.04, SD = 7.66, p = 0.02), a higher proportion of engaging in flexibility exercises (42.86% vs. 85.71%, p = 0.01) and a lower level of glycosylated hemoglobin (HbA1c) (mean reduction = 1.43%, SD = 2.54%, p = 0.03) at post-intervention. Conclusions: Delivering a low-dose MBSR intervention to prediabetes/diabetes patients in a primary care setting is feasible. Future studies with randomized controlled design and larger sample are warranted.